Patient- and Health-Care-Provider-Reported Outcomes to Consider in Research on Pregnancy-Associated Venous Thromboembolism - King, Alexandria; Leider, Haley; Herman, Dylan; Malinowski, Ann Kinga; D'Souza, Rohan (Thrombosis and Haemostasis, 2021)
Background Venous thromboembolism (VTE) in pregnancy can have numerous adverse impacts on patients and health care systems. Ongoing research aimed at improving maternal and fetal/neonatal outcomes is hampered by the lack of patient perspective in determining which outcomes are considered important to assess the effectiveness of interventions.Objectives The objective of this study was to elicit outcomes from those who experienced or were at risk for pregnancy-associated VTE (health service users, HSUs) and health care providers (HCPs) involved in their care.Methods Canadian HSUs and HCPs were recruited using convenience and purposive sampling, respectively. Individual, semistructured interviews aimed specifically at eliciting pregnancy-related outcomes were conducted until data saturation was attained. Interviews were audio-recorded and transcribed verbatim. Written transcripts were de-identified and interpretatively analyzed in duplicate to obtain outcomes related to participant experiences. Outcomes were grouped based on a taxonomy developed for medical research and compared between and across interviews with patients and HCPs, and with those obtained through a systematic review of the published literature.Results and Conclusion We interviewed 10 HSUs and eight HCPs and elicited 52 outcomes, 21 of which have not been reported in the literature. Although the majority of elicited outcomes were in the clinical/physiological core outcome area, both HSUs and HCPs highlighted the importance of outcomes related to functioning/life impact and general wellbeing of mother and baby. These outcomes representing the perspectives of HSUs and HCPs should be considered while conducting trials on pregnancy-associated VTE.
Keywords: outcome measures; pregnancy; qualitative research; venous thromboembolism